A Companion to the Patriarchate of Constantinople
1 online resource.
Keywords: This volume provides an overview of the development of the Patriarchate of Constantinople from Late Antiquity to the Early Ottoman period (4th to 15th c.). It highlights continuities and changes in the organizational, dogmatic, and intellectual framework of the central ecclesiastical institution of the Byzantine Empire in the face of political and religious upheavals. The volume pays attention to the relations of the Patriarchate with other churches in the West and in the East. Across the disciplinary divide between Byzantine and Ottoman studies, the volume explains the longevity of the Patriarchate beyond the fall of Byzantium in 1453 up to modern times. A particular focus is laid on an original register book of the 14th century. Contributors are: Claudia Rapp, Frederick Lauritzen, Tia M. Kolbaba, Johannes Preiser-Kapeller, Marie-Hélène Blanchet, Dimitrios G. Apostolopoulos, Machi Païzi-Apostolopoulou, Klaus-Peter Todt, Mihailo S. Popović, Konstantinos Vetochnikov, Ekaterini Mitsiou, Vratislav Zervan, and Christian Gastgeber.